2012
DOI: 10.1155/2012/786132
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and Adenomyosis

Abstract: Classically, the diagnosis of adenomyosis has only been possible on a hysterectomy specimen, usually in women in their late fourth and fifth decades, and, therefore, evaluating any relationship with infertility was simply not possible. As a consequence, to this day, no epidemiologic data exists linking adenomyosis to a state of subfertility. Today, new imaging techniques have enabled a noninvasive diagnosis at a much earlier time and a number of single-case or small series reports have appeared showing that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(128 citation statements)
references
References 78 publications
(86 reference statements)
3
121
0
1
Order By: Relevance
“…In women with adenomyosis, Hoxa 10 gene expression is decreased during the secretory phase of the cycle 7 .…”
Section: C) Abnormal Intraendometrial Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In women with adenomyosis, Hoxa 10 gene expression is decreased during the secretory phase of the cycle 7 .…”
Section: C) Abnormal Intraendometrial Metabolismmentioning
confidence: 99%
“…In women with endometriosis, an abnormal inflammatory response seems to exist in endometrium and impair implantation 7 .…”
Section: B) Altered Endometrial Receptivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomyosis is a uterine dysfunction characterized by the presence of endometrial glands with stromal elements in the myometrium (Azziz 1989, Campo et al 2012) but the etiology of this disorder is still unclear (Ferenczy 1998, Korzekwa et al 2014. Our previous studies showed that in cows the freCorrespondence to: A. Korzekwa, e-mail: a.korzekwa@pan.olsztyn.pl, tel.…”
Section: Introductionmentioning
confidence: 99%
“…During adenomyosis in cows, protein expression of the 17-beta estradiol (E2) receptor α (ERα) is increased and blood and endometrial E2 concentrations are elevated, indicating hormonal abnormalities during this condition (Campo et al 2012). Invasion by adenomyotic stromal cells was higher after E2 treatment in an in vitro model of stromal and myometrial co-culture of human cells .…”
Section: Introductionmentioning
confidence: 99%